Optomechanical terahertz detection with single meta-atom resonator. Issue 1 (December 2017) - Belacel, Cherif; Todorov, Yanko; Barbieri, Stefano; Gacemi, Djamal; Favero, Ivan; Sirtori, Carlo
Abstract Most of the common technologies for detecting terahertz photons (>1 THz) at room temperature rely on slow thermal devices. The realization of fast and sensitive detectors in this frequency range is indeed a notoriously difficult task. Here we propose a novel device consisting of a subwavelength terahertz meta-atom resonator, which integrates a nanomechanical element and allows energy exchange between the mechanical motion and the electromagnetic degrees of freedom. An incident terahertz wave thus produces a nanomechanical signal that can be read out optically with high precision. We exploit this concept to demonstrate a terahertz detector that operates at room temperature with high sensitivity and a much higher frequency response compared to standard detectors. Beyond the technological issue of terahertz detection, our architecture opens up new perspectives for fundamental science of light–matter interaction at terahertz frequencies, combining optomechanical approaches with semiconductor quantum heterostructures. Achieving fast, sensitive and room temperature detection of terahertz waves remains a formidable scientific and technological challenge. Here, the authors propose a compact terahertz device combining concepts from metamaterial resonators, optomechanics and semiconductor nanotechnology.